Periosteal Ewing's Sarcoma: Report of Two New Cases and Review of the Literature. (1999) - Kollender, Yehuda; Shabat, Shay; Nirkin, Alexander; Issakov, Josephine; Flusser, Gideon; Merimsky, Ofer; Meller, Isaac
Abstract : Background. The origin of Ewing's sarcoma in a periosteal location is rare and not clearly documented. Other malignant bone tumors appear to have a somewhat better prognosis when confined between periosteum and bone. Is it the same for periosteal Ewing's sarcoma? Methods. We describe two new cases and comprehensively review the literature consisting of 18 documented cases since the condition was first described in 1986 (S.M. Bator. Cancer 58:1781– 4). Results. Periosteal Ewing's sarcoma differs from the other forms of Ewing's sarcoma in terms of sex predominance, location of tumor, surgical stage at presentation and typical imaging studies. Eighteen out of the 20 patients were reported to be alive with no evidence of disease. Conclusions. It seems that the prognosis of this rare variant of Ewing's sarcoma family of tumors might be better but the small number of cases precludes such a firm conclusion.